2017
DOI: 10.1159/000458416
|View full text |Cite
|
Sign up to set email alerts
|

Stingless Bee Honey, the Natural Wound Healer: A Review

Abstract: Background: The stingless bee is a natural type of bee that exists in almost every continent. The honey produced by this bee has been widely used across time and space. The distinctive feature of this honey is that it is stored naturally in the pot (cerumen), thus contributing to its beneficial properties, especially in the wound healing process. Methods: In this article, several studies on stingless bee honey that pointed out the numerous therapeutic profiles of this honey in terms of its antioxidant, antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
155
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(159 citation statements)
references
References 86 publications
2
155
0
2
Order By: Relevance
“…can be found in Malaysia (Salim et al, ), in which Heterotrigona itama , a subgenus of Trigona, is often reared by local beekeepers. Several scientific reports and anecdotes (Abu Bakar, Sanusi, Abu Bakar, Cong, & Mian, ; Halcroft, Spooner‐Hart, Haigh, Heard, & Dollin, ; Ismail, ; Ismail & Ismail, ) have reported that stingless bee honey has the potential to generate a comfortable income for the beekeepers and add value to the functional food industry due to its high nutritional content (Vit, Medina, & Enriquez, ), good antioxidant properties (Biluca et al, ; da Silva et al, ; Harif Fadzilah, Jaapar, Jajuli, & Wan Omar, ; Kek, Chin, Yusof, Tan, & Chua, ), and antimicrobial activities (Abd Jalil, Kasmuri, & Hadi, ; Boorn et al, ; Choudhari, Punekar, Ranade, & Paknikar, ; Torres, Garedew, Schmolz, & Lamprecht, ; Zainol, Mohd Yusoff, & Mohd Yusof, ). Garedew, Schmolz, and Lamprecht (), Vit et al (), and Rosales () reported that stingless bee honey could potentially be used as a remedy for many illnesses such as stomach and intestinal ulcers, mouth diseases, sore throats, and for wound dressing in Ethiopia and other countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…can be found in Malaysia (Salim et al, ), in which Heterotrigona itama , a subgenus of Trigona, is often reared by local beekeepers. Several scientific reports and anecdotes (Abu Bakar, Sanusi, Abu Bakar, Cong, & Mian, ; Halcroft, Spooner‐Hart, Haigh, Heard, & Dollin, ; Ismail, ; Ismail & Ismail, ) have reported that stingless bee honey has the potential to generate a comfortable income for the beekeepers and add value to the functional food industry due to its high nutritional content (Vit, Medina, & Enriquez, ), good antioxidant properties (Biluca et al, ; da Silva et al, ; Harif Fadzilah, Jaapar, Jajuli, & Wan Omar, ; Kek, Chin, Yusof, Tan, & Chua, ), and antimicrobial activities (Abd Jalil, Kasmuri, & Hadi, ; Boorn et al, ; Choudhari, Punekar, Ranade, & Paknikar, ; Torres, Garedew, Schmolz, & Lamprecht, ; Zainol, Mohd Yusoff, & Mohd Yusof, ). Garedew, Schmolz, and Lamprecht (), Vit et al (), and Rosales () reported that stingless bee honey could potentially be used as a remedy for many illnesses such as stomach and intestinal ulcers, mouth diseases, sore throats, and for wound dressing in Ethiopia and other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Garedew, Schmolz, and Lamprecht (), Vit et al (), and Rosales () reported that stingless bee honey could potentially be used as a remedy for many illnesses such as stomach and intestinal ulcers, mouth diseases, sore throats, and for wound dressing in Ethiopia and other countries. Recently, two reviews were performed by Abd Jalil et al () and Rao, Krishnan, Salleh, and Gan () on the wound healing properties of honey and the biological and therapeutic values of the honeybee and stingless bee honey, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ancient Egyptians, Chinese, Greeks, and Romans utilized honey to cure the diseases of the intestine and skin wounds [1]. The previous study showed that honey can act as antioxidant, antimicrobial and anti-inflammatory [2].…”
Section: Introductionmentioning
confidence: 99%
“…Beekeepers of stingless bees can increase honey production by building a human-made hive to control the colony. This is since they are not revolt in picking the spot to construct hive [2]. There are around 500 species of stingless bees have been identified [4].…”
Section: Introductionmentioning
confidence: 99%